A randomized, placebo‐controlled trial evaluating effects of lebrikizumab on airway eosinophilic inflammation and remodelling in uncontrolled asthma (CLAVIER). Issue 12 (4th October 2020) - Austin, Cary D.; Gonzalez Edick, Melissa; Ferrando, Ronald E.; Solon, Margaret; Baca, Miriam; Mesh, Kathryn; Bradding, Peter; Gauvreau, Gail M.; Sumino, Kaharu; FitzGerald, J. Mark; Israel, Elliot; Bjermer, Lief; et al.
Abstract: Background: The anti‐interleukin 13 (IL‐13) monoclonal antibody lebrikizumab improves lung function in patients with moderate‐to‐severe uncontrolled asthma, but its effects on airway inflammation and remodelling are unknown. CLAVIER was designed to assess lebrikizumab's effect on eosinophilic inflammation and remodelling. Objective: To report safety and efficacy results from enrolled participants with available data from CLAVIER. Methods: We performed bronchoscopy on patients with uncontrolled asthma before and after 12 weeks of randomized double‐blinded treatment with lebrikizumab (n = 31) or placebo (n = 33). The pre‐specified primary end‐point was relative change in airway subepithelial eosinophils per mm 2 of basement membrane (cells/mm 2 ). Pre‐specified secondary and exploratory outcomes included change in IL‐13‐associated biomarkers and measures of airway remodelling. Results: There was a baseline imbalance in tissue eosinophils and high variability between treatment groups. There was no discernible change in adjusted mean subepithelial eosinophils/mm 2 in response to lebrikizumab (95% CI, −82.5%, 97.5%). As previously observed, FEV1 increased after lebrikizumab treatment. Moreover, subepithelial collagen thickness decreased 21.5% after lebrikizumab treatment (95% CI, −32.9%, −10.2%), and fractional exhaled nitric oxide, CCL26 and SERPINB2 mRNA expression in bronchial tissues also reduced. Lebrikizumab was well tolerated, with a safety profile consistent with other lebrikizumab asthma studies. Conclusions & Clinical Relevance: We did not observe reduced tissue eosinophil numbers in association with lebrikizumab treatment. However, in pre‐specified exploratory analyses, lebrikizumab treatment was associated with reduced degree of subepithelial fibrosis, a feature of airway remodelling, as well as improved lung function and reduced key pharmacodynamic biomarkers in bronchial tissues. These results reinforce the importance of IL‐13 in airway pathobiology and suggest that neutralization of IL‐13 may reduce asthmatic airway remodelling. Clinical Trial Registration: NCT02099656.